LEXICAL COHESION IN BUILDING THE COHERENCE IN THE “TIM FERRISS” PODCAST: STUDY OF SPOKEN DISCOURSE - Nehe, Imeldayanti; Ambalegin, Ambalegin (IdeBahasa, 2025)
This research aimed to identify the lexical cohesion in the “Tim Ferriss” podcast. The researchers adhered to the theory of Paltridge (2012) regarding lexical cohesion. There are six types of lexical cohesion introduced by Paltridge (2012). The research design was qualitative. The observational method and note-taking technique were employed to collect the research data. There were several steps in collected data, the researchers watched the entire interviewing podcast, then the researchers took notes and transcribed the spoken discourse. Next, the researchers highlighted the data base on the theory. In analyzing the data, this research used referential identity method and a coding process in the analysis of data. There several steps in analyzing data, the researchers read carefully the highlighted data. Next, the researchers coded data by marking and give number to data based on the research questions. Then researchers reduced the extensive data by selecting the main data. Finally, the researchers analyzed and identify the selected main data base on the research theory. The results of this research were clarified and displayed informally in the form of words to sentences. The results revealed the reference was the frequently utilized in the podcast due to the speaker and the hearer commonly refer to persons, things, proximity and describe comparisons between instances or elements in the discourse.